Choice of Performance Measures and Performance of Textile Sector in Bangladesh - Hossain, Mohammad Mobarak; Tabassum, Tahsina (Asian Business Review, 2019)
This study seeks out to establish the influence of quality as well as performance-based manufacturing strategy, diverse in performance measures, firm’s size, their interrelationship, and joint effects with the subjective measures on textile firm’s performance. Financial, objective, subjective, and non-financial measures have been taken into consideration. Bangladesh needs competitive strategies and measures to meet the challenges & opportunities for creating a sustainable position in the global market. Performance measures have been taken by the textile industries of Bangladesh to improve the performance. The influence of those measures is not always improving the performance as found in the earlier study. Responses from mid-level managers of 30 textile industries in Bangladesh have been taken into consideration using survey method using descriptive statistics, factor analysis, regression and correlation analysis. The result shows extensive use of measures and only subjective measures do not increase the performance of the industry, but customer-oriented measures, sustainability measures, manufacturing quality strategy with firm size increase the performance of the textile sectors. The study will open the scope of further exploration in the performance of the textile sector of Bangladesh.JEL Classification Code: G 21
Keywords: Measures; performance; choices; sustainability